2018
DOI: 10.1536/ihj.17-360
|View full text |Cite
|
Sign up to set email alerts
|

Improved Propensity-Score Matched Long-Term Clinical Outcomes in Patients with Successful Percutaneous Coronary Interventions of Coronary Chronic Total Occlusion

Abstract: The objective of the study was to evaluate major adverse cardiovascular events (MACE) after successful versus failed percutaneous coronary intervention for chronic total occlusion (PCI-CTO).Limited data are available on long-term clinical follow-up in the treatment of chronic total occlusion (CTO).Between January 2009 and December 2010 PCI-CTO was attempted in 283 consecutive patients with 289 CTO lesions. Procedural success was 62.3% and clinical follow-up covered 83% (235/283) of the study population with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…The presence of well-developed collaterals was associated with a significantly higher likelihood of procedural success, which has previously been associated with significantly improved prognosis. 37) The most commonly used scoring tool for predicting successful CTO PCI, the J-CTO score, 13) does not include the presence, maturity, or size of the vessel. The more recently described PRO-GRESS CTO score, 38) while it includes the presence or absence of "interventional collaterals" defined as collaterals which are amenable to crossing with a guidewire and microcatheter.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of well-developed collaterals was associated with a significantly higher likelihood of procedural success, which has previously been associated with significantly improved prognosis. 37) The most commonly used scoring tool for predicting successful CTO PCI, the J-CTO score, 13) does not include the presence, maturity, or size of the vessel. The more recently described PRO-GRESS CTO score, 38) while it includes the presence or absence of "interventional collaterals" defined as collaterals which are amenable to crossing with a guidewire and microcatheter.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these truly amazing technical improvements in achieving proficiency of CTO recanalization, many aspects of clinical efficacy of this demanding procedure remain controversial. Several non-randomized (observational) trials have shown that successful CTO revascularization could be linked to improved cardiovascular outcomes [15][16][17] and better quality of life (QOL) [18,19] . We have recently published a long term (66 months) follow-up of cohort of 283 patients in whom recanalization of CTO was attempted [20] .…”
Section: Symptomatic and Prognostic Impact Of The Pci For Ctomentioning
confidence: 99%
“…Several non-randomized (observational) trials have shown that successful CTO revascularization could be linked to improved cardiovascular outcomes [15][16][17] and better quality of life (QOL) [18,19] . We have recently published a long term (66 months) follow-up of cohort of 283 patients in whom recanalization of CTO was attempted [20] . Patients with successfully recanalized CTO had lower rate of MACE (defined as composite of cardiac mortality, myocardial infarction, and target vessel revascularization) than patients with failed procedure; the difference that remained statistically significant after adjustment for baseline between-group differences using propensity scores (adjusted HR 0.402; 95%CI: 0.196-0.824; P = 0.013).…”
Section: Symptomatic and Prognostic Impact Of The Pci For Ctomentioning
confidence: 99%
“…With the remarkable developments in interventional techniques in the last few years, the procedural success rate and safety of PCI in patients with CTO has improved [3][4][5]. Furthermore, successful PCI for CTO has been shown to reduce the risk of cardiac death, post-operative myocardial infarction (MI), and improves long-term survival compared with failed CTO PCI [6][7][8]. However, even after successful revascularization, the long term clinical outcomes of CTO patients were still unsatisfactory, and it has been identi ed as an independent predictor of the need for targetvessel revascularization (TVR) and subsequent adverse cardiac outcomes after CTO PCI [9,10].…”
Section: Introductionmentioning
confidence: 99%